Forty years of Soviet power : in facts and figures / Central Statistical Board of the U.S.S.R Council of Minister - Central Statistical Board of the U.S.S.R Council of Minister (Foreign Languages Publishing House, 1958)
319 hlm. : ilus. ; 21 cm.